Pengaruh umur pemotongan terhadap produktivitas gamal (Gliricidia sepium) - Mei Via Savitri; Herni Sudarwati; Hermanto Hermanto (Faculty of Animal Science, Universitas Brawijaya, 2013)
The purpose of the study was to determine the effect of cutting interval on production, and nutrition of gamal (Gliricidia sepium). The study was conducted on Agriranch sheep farm, Pandan Rejo Subdistrict, Bumi Aji District of Malang Regency from May 25th to August 25th 2012. Proximate Analysis was carried out at the Animal Nutrition Laboratory, Animal Husbandry Faculty, Brawijaya University. The study used Randomized Block Design (RBD) which consisted of four treatments and three cutting age groups. The treatments were U60 (60 days of cutting age), U80 (80 days of cutting age), U100 (100 days of cutting age), and U120 (120 days of cutting age). The study found that the lowest production of leaves, twigs, dry matter, organic matter, and fibre were at 60 days of cutting age. Meanwhile the highest production of them was at 120 days of cutting age. However, the lowest crude protein content was found at 120 days cutting age. The study suggests that gamal was able to provide better nutrition as animal forages at 80 days of cutting age. Keywords: Gliricidia sepium, cutting age, dry matter, organic matter, fibre